2009
DOI: 10.1016/j.jcrs.2009.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive keratectomy in eyes with atypical topography

Abstract: Laser correction of refractive errors is one of the most effective surgical procedures today. Even so, the selection of patients who will have the outcomes they expect remains a major challenge. Corneal ectasia, a frustrating problem that can occur naturally with diseases such as keratoconus, has also been reported after refractive surgery. This review addresses the issues surrounding the use of surface refractive surgery in patients who may have atypical topography, which is a risk factor for ectasia. At pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…This is similar to a study in India, which cited the same most common reasons for rejection of LASIK (20), and Table III compares their results with this study. Patients with thin corneas and normal corneal topography and refraction less than -5.00 D of myopia or thick cornea with mild suspicious corneal topographies were advised to have PRK (29). Patients with thin corneas and higher refractive errors and cases with >5% Klyce-Maeda KCI using the TMS-2 regardless of their refractive error were advised to have phakic intraocular lens implantation (30).…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to a study in India, which cited the same most common reasons for rejection of LASIK (20), and Table III compares their results with this study. Patients with thin corneas and normal corneal topography and refraction less than -5.00 D of myopia or thick cornea with mild suspicious corneal topographies were advised to have PRK (29). Patients with thin corneas and higher refractive errors and cases with >5% Klyce-Maeda KCI using the TMS-2 regardless of their refractive error were advised to have phakic intraocular lens implantation (30).…”
Section: Resultsmentioning
confidence: 99%
“…Pachymetry is an important test and is an indicator of corneal health, but varies widely in different ethnic populations 22. Patients with thin corneas, normal corneal topography and refraction less than -5.00 Diopters of myopia or thick cornea with mild atypical corneal topographies were advised to have PRK 23. Patients with thin corneas and higher refractive errors and cases with >5% Klyce-Maeda KCI using the TMS-2, regardless of their refractive error, were advised to have phakic intraocular lens implantation 24.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Silva Filho et al reported that preoperative topographic irregularities may predict the loss of corrected visual acuity in the postoperative period (20) . On the other hand, refractive surgery with high success rates and minimal adverse effects in patients with atypical or irregular topography has already been described in the literature (21,22) . A recent study reports the use of LASIK in eyes with suspected keratoconus on topography but confirmed as normal through epithelial thickness mapping with digital high frequency ultrasound (Artemis VHF, ArcScan Inc.); the patients were followed up for one year without developing ectasia (23) .…”
Section: Discussionmentioning
confidence: 99%